A Brief Introduction to Buddhism - Partridge, Christopher H. (Christopher Hugh), 1961-; Dowley, Tim (Book collections on Project MUSE., 2018)
This brief introduction to Buddhism is designed to help readers understand this important religious tradition. Known and valued for its balanced approach, this text provides coverage of Buddhism through an arresting layout with rich colors. The content is enhanced by charts of religious festivals, historic timelines, updated maps, and a useful glossary. It is ideal for courses on Buddhism and Asian religions and will be a useful reference for all readers eager to learn more.